Bimetallic oxide derived from metal organic framework (MOF) as potential electrode materials for supercapacitor / Farah Juliana Juni - Farah Juliana , Juni (2021)
Metal oxide is one of the promising electrode materials due to higher capacitance capabilities, higher energy density, low manufacturing cost and easy processability. However, due to major changes of structure and phase during charge-discharge, the performance of the devices will be degraded. In this research, a highly controllable nanostructure of metal oxide was synthesized using a new molecular building blocks with porous structure called metal-organic framework (MOF) as the self-sacrificing template. 2-methylimidazole was reacted with copper ions via co-precipitation method to produce Cu-MOF which exhibits capacitance value of 35 Fg-1 at current density of 0.25 Ag-1. The capacitance value of the electrode was then able to increase through addition of secondary metal, cobalt (CuCo-MOF). The shale-shaped microcrystal copper cobalt nitrate hydroxide exhibits capacitance value of 179 Fg-1 at current density of 0.25 Ag-1. Finally, Cu-MOF and CuCo-MOF were calcined under nitrogen flow at temperatures of 700, 800 and 900 °C to derive the metal oxides and were verified by XRD and XPS results. Oxide obtained at 900 °C (CuMOF-900) exhibited the highest capacitance values of 585 Fg-1 at current density of 0.25 Ag-1. This might be due to the richer oxidant and reductant taking place during the charging and discharging process. However, CuCo-700 was observed to be the most stable since the electrode can retain up to 98 % after 2500 cycles at reversible current densities of 0.25, 0.35 and 0.45 Ag-1. Metal oxide derived from bimetallic-OF proved to enhance the capacitive performance of the electrode materials due to porous structure and richer oxidant and reductant.